Ibiza durante el reinado de Felipe IV, 1621-1665. Entre la problemática defensiva y la supervivencia - Espino López, Antonio (Cuadernos de Historia Moderna, 2006)
In this article, we have dealt with a neglected subject: the defence of the Spanish Mediterranean during the reign of Philip IV (1621-1665), focusing on the isle of Ibiza. Through the XVI th Century, some measures of defence were adopted to try to stop the danger represented by the North-African corsairs. Notwithstanding, during the reign of Philip IV, to this traditional muslim enemy, the no less traditional French enemy was added. This French enemy, seling the bad defences of the place and the strategical importance of Ibiza, started to press over the island from the 1660s onwards.